Effect of Auditor Ethics, Complexity, Audit Fees, Auditor Motivation, and Time Budget Pressure on Audit Quality for All Members of the Indonesian Institute of Certified Public Accountants - Abdul Aziz; Iskandar Muda; Chandra Situmeang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of auditor ethics, complexity, audit fees, auditor motivation, and time budget pressure on audit quality for All Members of the Indonesian Institute of Certified Public Accountants. This research is a quantitative research with a descriptive approach. The research was carried out in All Members of the Indonesian Institute of Certified Public Accountants who are registered in the 2020 membership. The population of this study were All Members of the Indonesian Institute of Certified Public Accountants as many as 1,450 people. The sample size in this study was 208 Members of the Indonesian Institute of Certified Public Accountants. This research uses structural equation model (SEM) analysis. The results obtained are that auditor ethics has a significant effect on audit quality, complexity has a significant effect on audit quality, audit fees has a significant effect on audit quality, auditor motivation has a significant effect on audit quality, and time budget pressure has a significant effect on audit quality.